Structural brain correlates of resilience to traumatic stress in Dutch police officers. (November 2017) - van der Werff, Steven J.A.; Elzinga, Bernet M.; Smit, Annika S.; van der Wee, Nic J.A.
Highlights: Resilience to trauma is related to increases in white matter integrity. White matter tracts involved included the corticopontine tract. Structural connectivity is related to positive reappraisal of stressful experiences. Abstract: Objective: Neurobiological research has traditionally focused on vulnerability rather than on resilience to severe stress. So far, only a few neuroimaging studies examining resilience have used designs that allow disentangling of the neural correlates of resilience from those related to psychopathology or trauma-exposure. The aim of this study was to identify structural brain correlates of resilience, and their correlations with behavioral measures. Method: MRI scanning was performed in three groups of police officers: (1) a resilient group (N = 29; trauma-exposed, no psychopathology), (2) a vulnerable group (N = 33; trauma-exposed, psychopathology), and (3) a control group (N = 19; no trauma, no psychopathology). Using whole brain and region-of-interest approaches, we examined gray matter volume and shapes, and white matter integrity using software tools from the FSL-library. Results: We did not find patterns of gray matter volumes or shape specific for the resilient group. In resilient police officers, we found an increase in structural connectivity in the corticopontine tract. White matter integrity in this location correlated with a coping style of positive reappraisal. Conclusions: Resilient police officers show a specific pattern of increased structural connectivity, which is associated to the use of higher order emotion regulation strategies. Given this finding in an area that has not been implicated in stress-related disorders before, as well as the null findings in areas repeatedly shown to be involved in stress-related disorders, the current study indicates that resilience is not simply the opposite of having psychiatric symptoms, but rather an independent construct.